PP077 Intravitreal Corticosteroids In Macular Edema: Quality Of The Evidence. (12th January 2018) - Marchetti, Marco; Oradei, Marco; Ruggeri, Matteo; Navarra, Pierluigi; Urbina, Luz Irene
Abstract : INTRODUCTION: Treatment options for macular edema include intravitreal corticosteroids (1). Traditionally, an injectable suspension of triamcinolone acetonide (TA) had been employed off-label (2); in recent years, authorities have approved sustained-release drug delivery systems (DDSs) for corticosteroids (3). Considering the hypothesis that the use of these drugs is based on widely variable evidence in terms of methodological quality and robustness, the purpose of this analysis is to compare the quality of the evidence on efficacy and safety of three different formulations of intravitreal corticosteroids: the dexamethasone (DEX) implant, the fluocinolone acetonide (FA) implant, and the preservative-free injectable suspensions of TA, in the management of two retinal pathologies: diabetic macular edema (DME) and macular edema secondary to retinal vein occlusion (RVO). METHODS: A search of clinical trials on MEDLINE from 1 January 2000 to 16 December 2015 was performed. Studies were included in the analysis if they met the following criteria: (i) related to at least one of the preparations of interest in patients with DME or macular edema secondary to RVO; (ii) included a control group treated with placebo, observation, sham procedures or conventional treatments; and (iii) included visual acuity, retinal thickness and/or safety parameters as outcomes. Results were summarized in a narrative manner. RESULTS: Twenty-five publications from nineteen RCTs were included. We observed increased attention of researchers towards TA compared to DEX and FA; however, studies for TA are less robust. Scientific publications related to DEX and FA implants are of higher quality, especially in terms of randomization and masking procedures. CONCLUSIONS: Even though each of the three considered corticosteroid-containing medicines are approved for marketing and included in clinical guidelines for treatment of macular edema, a high degree of heterogeneity in terms of quality of evidence has been noticed among them. This observation underlines the need to review the requirements for drug approval and their inclusion in clinical recommendations, as well as the importance of post-markeing monitoring to generate new evidence.